Nawa al-Saâdawi: Modalitas sebagai Pembentuk Nilai Islam dalam Praktik Diskursus Gender oleh Pemimpin Agama dan Penguasa Mesir - Fauziyah, Yayuk (Program Pascasarjana UIN Sunan Ampel Surabaya, 2008)
Nawa al-Saâdawi is an Egyptian gender and social activist. Her first and most controversial novel âal-Marâah wa al-Jinsâ provoked a far-reaching debate on issues relating to sex and women. This novel was the reason for her intimidation by both the political and religious authorities in Egypt. She was later dismissed from her position as a director of public health service by the request of the political authority. To her disappointment, Egypt was overwhelmed by a repressive mentality of men against women and children. And she believed that this repression was the result of âamong others- the capitalistic mentality of the Egyptians. This mentality was translated into a discourse that legitimizes gender-bias policy that both political and religious authorities advocated. Al-Saâdawi objected this, and expressed her concern in her The Hidden Face of Eva where she first narrates the repressive reality that she encounters in her society. She then suggests that the capitalistic mentality of the Egyptians has become some kind of value system around which their behavior was shaped. By value system she means a belief that women can â and even must- be exploited for the interest of men. Woman is inferior to man. This belief is so common that it forms part and parcel of the Egyptian social structure, mentality and the way they run their day-to-day economic activities. A patriarchal society would stand firm in defense of this value system. Driven either by its capitalistic mentality or else by its persistence to stay resolute, the patriarchal society would unduly remain aloof in its exploitation of women and children. The thrust of al-Saâdawiâs ideas is to challenge all this. This paper in the meantime is destined to explore those ideas by consulting the Islamic view concerning justice and equality. We also are interested in examining al- Saâdawiâs ideas by employing Pierre Bourdieuâs schemata of Habitus x Capital = Domain.